Luce - Watts, Naomi, 1968-; Spencer, Octavia; Roth, Tim; Harrison, Kelvin, Jr., 1994-; Butz, Norbert Leo; Bang, Andrea; Blake, Marsha Stephanie (Universal City, CA : Universal Pictures Home Entertainment, 2019)
Garnering recognition for his stellar athletic abilities and intellectual accomplishments "Luce" follows the titular characters struggle of maintaining his integrity while dealing with the circumstances of his background. Adopted from a war-torn country just ten years prior, Luce becomes the very essence of what many consider to be the American Dream. However, all changes when his teacher encounters a shocking revelation upon examining the contents of Luce's locker. Luce is then charged with fighting to maintain his integrity and reputation, as everyone around him begins to question his true character and motives.
Language and subtitle options taken from DVD menu screen. Container indicates disc includes DVS Dolby Digital 2.0 track but this track is not present.
Title from title frame.
Based on the play by JC Lee.
Originally released as a motion picture in 2019.
Wide screen (2.39:1).
Bonus features: Feature commentary with director Julius Onah; Interview with Octavia Spencer and Naomi Watts.
Keywords: Drama films; High school students -- Drama; Parent and child -- Drama; Adopted children -- Drama; Families -- Drama